A Method of Reducing Cogging Torque by Using Magnet Shifting Angle in Permanent Magnet Motor - Mohd Zamurina, Nurul Nabila; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2022)
Cogging torque is an unwanted element in the PMM. It can cause many problems such as noise, vibration and speed ripple. In this study, the permanent magnet angle shifting method has been chosen to reduce cogging torque for permanent magnet motor by using JMAG software. PM angle shifting method is a method where PM is moving apart from each other according to the accurate angle. Three design of PM was investigated in this research to determine the reduction of cogging torque value in the PMM. In conclusion, cogging torque of PMM is reduced by 29.4% compared to the previous PMM without the angle shifting method.